Behavioral Conceptual Framework of Debt Decision-Making Among B40 Households in Malaysia: Insights from Skinner and Watson: Kerangka Konseptual Tingkah Laku Terhadap Pembuatan Keputusan Hutang Dalam Kalangan Isi Rumah B40 Di Malaysia: Tinjauan Daripada Skinner Dan Watson - Sulong, Amri; Raja Yusof, Raja Nor Azuwah (Journal of Human Capital Development (JHCD), 2025)
The rapid expansion of online lending platforms has significantly increased access to short-term credit, particularly among Malaysia’s B40 population. While this convenience addresses immediate financial needs, it also raises concerns regarding behavioural and financial sustainability. This theoretical essay examines debt-related decision-making among B40 households through the lens of behavioural psychology, drawing on the concepts of B. F. Skinner and John B. Watson. From a behaviourist perspective, external stimuli such as financial stress, social expectations, and easy access to credit influence borrowing and repayment behaviours. Skinner’s reinforcement theory further explains how repeated borrowing is sustained through positive reinforcement, such as temporary financial relief, and negative reinforcement, such as avoiding social pressure. The framework suggests that debt behaviour is not solely an economic choice but a learned response shaped by environmental conditioning. The study underscores the importance of behaviour-based financial interventions to promote sustainable financial well-being among vulnerable households.